Measuring Exchange Market Pressure and Its Contagion in the East African Community. (20th June 2013) - Hegerty, Scott W.
Abstract As the members of the East African Community seek to further integrate their economies, issues of compatibility arise. How interlinked are these countries' exchange markets, and which currencies are most likely to influence their neighbours? This study constructs monthly indices of exchange market pressure (EMP) for Burundi, Kenya, Rwanda, Tanzania and Uganda over the past decade. Two methods of constructing these indices are shown to exhibit large differences. Vector autoregressive approaches are then applied to the main EMP series and a set of global stock price proxies. Kenya, the dominant economy, is shown to have the largest effect on the region but is not itself affected by other regional currencies. Foreign stock price declines increase EMP for all countries except Tanzania, which is also the least integrated in terms of trade. This suggests that financial integration in the region is uneven – with implications for a successful common currency.